STRATEGI PENGEMBANGAN AGILE KNOWLEDGE WORKER DI DIVISI FINANCE PT PFIZER INDONESIA BERDASARKAN PERSPEKTIF HUMAN CAPITAL DAN KNOWLEDGE MANAGEMENT (The Development Strategic of Agile Knowledge Worker in Finance Division PT Pfizer Indonesia based on Human Capital and Knowledge Management Perspectives) - Eva Fauziana (Institut Bisnis Muhammadiyah Bekasi, 2020)
Radical and global changes in the world and also the fast development of knowledge economy era (Drucker, 1990) affected and forced all profit and non-profit organizations to be radically adaptive to the changes. Pfizer Inc, as one of the biggest pharmaceutical corporation in the world, also aware the needs to be adaptive in the radical change. Led be new CEO, Mr. Jeffrey B. Kindler, Pfizer keeps on enhancing and improving itself by conducting Pfizer transformation since early 2006. For Pfizer People, transformation is not a short cut process of reduction costs and restructurization, but transformation are mainly focused to develop healthier and better environment in the world as stated in Pfizer new motto in 2016: “Working for Healthier WorldTM” In finance division PT Pfizer Indonesia, the improvement and enhancement process are led by conducting Finance Survey in 2006. The survey becomes the basic evaluation and the key indicator as Finance Performance. From some theories on human capital compiled with other theories, references and understanding on knowledge management, change management, culture management, learning organization and agile leadership, I summarize the new concept of agile knowledge worker. I strongly support that the limitation of this new concept can be the new thoughts and ideas of the human capital and knowledge management development and implementation